Sensitivity of the Cervical Disc Loads, Translations, Intradiscal Pressure, and Muscle Activity Due to Segmental Mass, Disc Stiffness, and Muscle Strength in an Upright Neutral Posture - Arshad, Rizwan; Schmidt, Hendrik; El-Rich, Marwan; Moglo, Kodjo (Frontiers in Bioengineering and Biotechnology, 2022)
Musculoskeletal disorders of the cervical spine have increased considerably in recent times. To understand the effects of various biomechanical factors, quantifying the differences in disc loads, motion, and muscle force/activity are necessary. The kinematic, kinetic or muscle response may vary in a neutral posture due to inter-individual differences in segmental mass, cervical disc stiffness, and muscle strength. Therefore, our study aimed to develop an inverse dynamic model of the cervical spine, estimate the differences in disc loads, translations, intradiscal pressure and muscle force/activity in a neutral posture and compare these results with data available in the literature. A head-neck complex with 9 segments (Head, C1-T1) was developed with joints having 3 rotational and 3 translational degrees of freedom, 522 nonlinear ligament fibers, and 254 muscle fascicles. A sensitivity analysis was performed to calculate the effect of segmental mass (5th to 95th percentile), the translational disc stiffness (0.5 to 1.5) and the muscle strength (0.5 to 1.5) on the cervical disc loads (C2-C3 to C7-T1), disc translations, intradiscal pressure and muscle force/activity in a neutral posture. Additionally, two axial external load conditions (0 and 40 N) were also considered on the head. The estimated intradiscal pressures (0.2-0.56 MPa) at 0 N axial load were comparable to in vivo measurements found in the literature, whereas at 40 N values were 0.39 to 0.93 MPa. With increased segmental mass (5th to 95th), the disc loads, translations, and muscle forces/activities increased to 69% at 0 N and 34% at 40 N axial load. With increased disc stiffness (0.5 to 1.5), maximum differences in axial (<1%) and shear loads (4%) were trivial; however, the translations were reduced by 67%, whereas the differences in individual muscle groups forces/activities varied largely. With increased muscle strength (0.5 to 1.5), the muscle activity decreased by 200%. For 40 N vs 0 N, the differences in disc loads, translations, muscle forces/activities were in the range of 52 to 129%. Significant differences were estimated in disc loads, translations, and muscle force/activity in the normal population, which could help distinguish between normal and pathological cervical spine conditions.